Untersuchung zum postoperativen Verlauf bei Patienten mit Hämophilie - Krekeler, S.; Alesci, S.; Miesbach, W. (Hämostaseologie, 2012)
Thromboembolic complications may occur in patients with major operations even after routine thromboprophylaxis with low-molecularweight-heparin. In this retrospective, single center survey the post-operative course of patients with haemophilia was investigated. Patients, methods Overall, the postoperative course in 85 patients with haemophilia A and B (median age: 43 years, 18–73 years) and 139 surgical procedures was analyzed. The surgical procedures mainly consist of major orthopedic surgery (58 total knee replacement, 15 hip replacement, 17 other major orthopedic surgery, 15 minor orthopedic procedures). Additional surgical procedures were abdominal-surgical (18), urological (8), neurosurgical (5). Results During the post-operative observation period a small number of wound healing complications occurred (4%). None of the patients developed symptomatic deep vein thrombosis or lung embolism. Conclusion There seems to a decreased risk of postoperative thromboembolism in patients with haemophilia.
Keywords: Haemophilia; thrombosis; surgery